Supportive Environment and Entrepreneurial Skills as Determining Factors for Entrepreneurial Career Preference among University Students in Nigeria (Global Business Management Review (GBMR), 2023)
Enterprise and entrepreneurial activities are seen as a most important factors for economic growth and development in the post COVID-19 pandemic era which is term here as the “New Era”. However, entrepreneurship education and training enhance individuals’ entrepreneurial skills and attitude, hence promote entrepreneurial career preference. The study was designed to explore the mediating effect of entrepreneurial Skills on the relationship between supportive environment and entrepreneurial career preference among university students in Nigeria. The population of the study consist of a total of 36, 798 final year students from four areas of studies across six universities in northern Nigeria. The study used structural equation modelling Smart-PLS (3.0) to analysis the data obtained from a sample of 395 final year students cross six universities to test the hypotheses. The study established a significant positive association between internal supportive environment and the students’ entrepreneurial career preference. However, the study found no significant association between external supportive environment and the students’ entrepreneurial career preference. In addition, the study established that entrepreneurial skills significantly mediate the association between internal supportive environment, external supportive environment and students’ entrepreneurial career preference. The study provided suggestion for future research.